2017
DOI: 10.1021/acs.inorgchem.7b00920
|View full text |Cite
|
Sign up to set email alerts
|

Chiral Discrimination of Diamines by a Binaphthalene-Bridged Porphyrin Dimer

Abstract: A pair of 1,1'-binaphthalene-bridged bisporphyrins, (R)- and (S)-H1, were designed to examine their chiral discrimination abilities toward a range of model diamines by using UV-vis absorption, CD, and H NMR spectroscopy with the assistance of DFT molecular modeling. The spectroscopic titrations revealed that (R)-/(S)-H1 could encapsulate (R)-/(S)-DACH and (R)-/(S)-PPDA in the chiral bisporphyrin cavities, leading to the selective formation of sandwich-type 1:1 complexes via dual Zn-N coordination interactions.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…Porphyrin dimers are well established as probes for chiral analyses. Therefore, in this case, we had the additional benefit of a comparison of our new results with a very similar and recently reported meso-tetraphenylporphyrin (TPP) analogue of our system [88], which was also used for chiral analysis. Lu et al [88] observed easy discrimination of the enantiomers of cyclohexane-1,2-diamine (CHDA), using their porphyrin-substituted 1,1 -binaphthyl dimer host, and was mirrored in our report using NMR spectroscopy and other methods.…”
Section: Coordination Complexesmentioning
confidence: 94%
See 1 more Smart Citation
“…Porphyrin dimers are well established as probes for chiral analyses. Therefore, in this case, we had the additional benefit of a comparison of our new results with a very similar and recently reported meso-tetraphenylporphyrin (TPP) analogue of our system [88], which was also used for chiral analysis. Lu et al [88] observed easy discrimination of the enantiomers of cyclohexane-1,2-diamine (CHDA), using their porphyrin-substituted 1,1 -binaphthyl dimer host, and was mirrored in our report using NMR spectroscopy and other methods.…”
Section: Coordination Complexesmentioning
confidence: 94%
“…Therefore, in this case, we had the additional benefit of a comparison of our new results with a very similar and recently reported meso-tetraphenylporphyrin (TPP) analogue of our system [88], which was also used for chiral analysis. Lu et al [88] observed easy discrimination of the enantiomers of cyclohexane-1,2-diamine (CHDA), using their porphyrin-substituted 1,1 -binaphthyl dimer host, and was mirrored in our report using NMR spectroscopy and other methods. Our report includes additional analytical possibilities for ee determination by using electronic spectrophotometry including UV-vis, CD and fluorescence emission methods.…”
Section: Coordination Complexesmentioning
confidence: 94%
“…Lu et al, reported in 2017 a chiral binaphthalene-bridged bisporphyrin with C2 symmetry (Figure 17a, XX) able to recognize chiral diamines in chloroform [80]. The CD spectra of the two enantiomer pairs point out a mirror image with a bisignate couplet in the porphyrin Soret region (Figure 17b).…”
Section: Bis-porphyrin Systems and Porphyrin-tweezersmentioning
confidence: 96%
“…[12][13][14][15][16][17][18][19][20][21][22][23][24][25] Initially, mono-porphyrins were used as chiral sensors, further bis-and tris-porphyrins as well as corresponding supramolecular assemblies were also applied for this purpose. [26][27][28][29][30][31][32][33] Generally, the chirality of the system is probed by circular dichroism (CD) spectroscopy. 12,[20][21][22][23] Recently, a combination of experimental and computational studies on the complexation of a chiral zinc(II) porphyrin tweezer with achiral aliphatic diamines highlighted a critical role played by the diamine guest in modulating the relative orientation of the two porphyrin rings and hence in coupling the electronic transition moments.…”
Section: Introductionmentioning
confidence: 99%